TRANSFORMASI PEMASARAN KEDAI KULINER : FOKUS PADA PROMOSI DAN PELAYANAN - Agus Sobar; Sugih Prakoso; Muhammad Zaky (PT. ABIG RIZKY PUBLISHER, 2025)
This research aims to analyze the influence of promotion and service quality on consumer purchase decisions at Kedai Abig Berkah Sukabumi. Facing intense competition in the culinary industry, businesses require precise marketing strategies, including effective promotion and quality service. Kedai Abig Berkah Sukabumi itself experienced a sales decline due to suboptimal promotion and service weaknesses. This study used a quantitative associative approach with 96 respondents as the sample. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS software. The results indicate that the promotion variable partially has a positive and significant influence on purchase decisions. The service quality variable also partially has a positive and significant influence on purchase decisions. Promotion and service quality simultaneously have a significant influence on consumer purchase decisions. These two variables, promotion and service quality, explain 40.9% of the variation in purchase decisions, while the remaining 59.1% is influenced by other factors outside these two variables. These findings emphasize the importance of effective promotion and improving service quality in encouraging and enhancing consumer purchase decisions.